2021
DOI: 10.1007/s10290-020-00401-2
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality and the quality of imports

Abstract: This paper studies the role of income inequality in the importing country as a determinant of export unit value and product quality estimated employing information on market shares and prices. Using detailed firm-level data, we find that higher inequality in the destination market is associated with lower unit value and product quality. Noticeably, the negative effect of inequality is stronger in richer destinations. Firm-level heterogeneous responses to market conditions explain changes in unit value and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…A 1 percent increase in food import reduces the income inequality by 0.29 percent. This is in synch with other studies such as Ciani (2017) and Otsuka (2013). Conversely, inflation and population growth are statistically significant at 5 percent and 1 percent respectively.…”
Section: Long-run Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…A 1 percent increase in food import reduces the income inequality by 0.29 percent. This is in synch with other studies such as Ciani (2017) and Otsuka (2013). Conversely, inflation and population growth are statistically significant at 5 percent and 1 percent respectively.…”
Section: Long-run Analysissupporting
confidence: 89%
“…The study reached this decision after employing the generalized method of moment. Ciani (2017) investigated the link between income inequality and food import using a heterogeneous trade model and found a positive relationship between income inequality and food imports. The same finding was found by Otsuka (2013) argued that food imports will solve hunger, create more income via the multiplier process and eventually solve income inequality.…”
Section: Brics Stylized Factsmentioning
confidence: 99%
“…When income changes have an impact on both export and import demand, the multiplier's value also varies because the multiplier's size is de ned by how consumption and investment react to income changes as a consequence of an automatic shift in demand. (Ciani, 2021). The excess aggregate demand brought on by expansionary monetary and scal policies has resulted in a balance of payments de cit, either through the expansion of imports to offset some of this excess or another portion (excess net demand), which has raised prices, increased imports, and decreased exports.…”
Section: Graphical Illustrationmentioning
confidence: 99%
“…Bekkers et al (2012) used panel data, including Turkey, and showed "the negative effect of inequality" on import unit values. Recently, Ciani (2021) found that income inequality plays a significant role in import demand by inducing "quality and unit value differentials across markets. " Various researchers have also estimated the Turkish import demand function.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, consumers' behavior matters in determining the import demand function (Mitra and Trindade, 2005). From this point of view, the influence of inequality on the import demand function has gained importance in the many research done so far (Mitra and Trindade, 2005;Adam, Katsimi and Moutos, 2012;Ciani 2021).…”
Section: Introductionmentioning
confidence: 99%